Women And Education: A Gynocritic Study of La Petite Fille Du Réverbère by Calixthe Beyala and Unpublished Manuscript by Ambai - R, Visalakshi.; Daniel, Antoinette; Khanjan; Mishra, Siddhartha (Journal of Cultural Analysis and Social Change, 2025)
This article focuses on the presentation of women, their hurdles in family life and professional life and how they gain their space and identity through education in the works of Calixthe Beyala and Ambai. Both the authors present in detail the atrocities of patriarchy and the marginalisation of women in the Afro-French society and the Tamil society. Elaine Showalter’s “Gynocriticism” theory is applied in this article to bring into light the socio-cultural pressures, resilience and self-establishment of the female protagonists in Beyala’s La petite fille du réverbère and Ambai’s Unpublished Manuscript .These two authors suggest education to be the best critical tool for women to assert their identity and claim their space with dignity. The analysis proves how education empowers women to proclaim and affirm their voices and overcome patriarchal domination, highlighting the themes of female solidarity, self-respect and identity issues. The article finally contributes to feminist literary criticism by focusing on women’s experiences and affirming the transformative power of education in the quest for gender equality.